Behavioral effects in disorders of consciousness following transcranial direct current stimulation: A systematic review and individual patient data meta-analysis of randomized clinical trials - Xu, Zeyu; Zheng, Ruizhe; Xia, Tiantong; Qi, Zengxin; Zang, Di; Wang, Zhe; Wu, Xuehai (Frontiers in Neurology, 2022)
Background: In patients with Disorders of Consciousness (DoC), recent evidence suggests that transcranial direct current stimulation (tDCS) seems to be a promising intervention for them. However, there has been little agreement about the treatment effect and the optimal treatment strategy of the tDCS in the DoC. Objective: In this meta-analysis of individual patient data (IPD), we assess whether tDCS could improve DoC patients' behavioral performance. We also determine whether this treatment effects could be modified by patient characteristics or tDCS protocol. Methods: We searched PubMed, Embase, and the Cochrane Central Register of Controlled Trials through April 7, 2022, using the terms “persistent vegetative state,” “minimally conscious state,” “disorder of consciousness,” or “unresponsive wakefulness syndrome,” and “transcranial direct current stimulation” to identify Randomized Controlled Trials (RCTs) in English-language publication. Studies were eligible for inclusion if they reported pre- and post-tDCS Coma Recovery Scale-Revised (CRS-R) scores. From the included studies, any patients who had incomplete data were excluded. We performed a meta-analysis to assess the treatment effect of the tDCS compared with sham control. Additionally, a subgroup analysis was performed to determine whether patient characteristics could modify the treatment effect and to find out the optimal tDCS protocol. Results: We identified 145 papers, eight trials (including 181 patients) were finally included in the analysis, and one individual data were excluded because of incomplete data. Our meta-analysis demonstrated a mean difference change in the CRS-R score of 0.89 (95% CI, 0.17-1.61) between tDCS and sham-control, favoring tDCS. The subgroup analysis showed that patients who were male or with a minimally conscious state (MCS) diagnosis were associated with a greater improvement in CRS-R score. We also found that patient who underwent 5 or more sessions of tDCS protocol might have a better treatment effect than just one session. Conclusion: The result shows that the tDCS can improve the behavioral performance of DoC patients. The heterogeneity of the treatment effect existed within the patients’ baseline condition and the stimulation protocol. There should be more exploration about the optimal tDCS protocol and the most beneficial patient group based on the mechanism of tDCS in the future.